2010
DOI: 10.1007/s10853-010-4447-y
|View full text |Cite
|
Sign up to set email alerts
|

Particle cavitation in rubber toughened epoxies: the role of particle size

Abstract: Rubber toughened epoxies are used in a wide range of applications including adhesives when toughness is a crucial property. It is well known that the cavitation of the rubber particles is an important process to optimise the toughness of such materials. This paper describes the development of a predictive model to describe the dependence of rubber particle cavitation on particle size. The model is developed using a combination of experimental observations and finite element simulations.Predictions have been ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 32 publications
0
29
1
Order By: Relevance
“…There are several reasons that may cause this. The lack of plastic deformation of the epoxy could be a direct result of the lack of strain energy build up due to such early debonding, thus slowing the growth of shear bands and voids [44,45]. Alternatively, these high aspect ratio GNPs have sharp edges which effectively act as defects and leads to fracture at low loads, hence low fracture toughness.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reasons that may cause this. The lack of plastic deformation of the epoxy could be a direct result of the lack of strain energy build up due to such early debonding, thus slowing the growth of shear bands and voids [44,45]. Alternatively, these high aspect ratio GNPs have sharp edges which effectively act as defects and leads to fracture at low loads, hence low fracture toughness.…”
Section: Discussionmentioning
confidence: 99%
“…Rey et al [45] have pointed out that this is approximately -60°C for the polysiloxane found in the CSR particles in the current work. This increase in the cavitational resistance of the particles limits the dissipation of energy via the plastic void growth mechanism, although computational studies by Guild et al [46] have demonstrated that rubber particles cavitating at higher strains cause a far more complex shear-band dissipation mechanism and this can offset the loss of effectiveness of the void growth mechanisms. Finally, the increased resistance to plastic deformation of the matrix at the lower temperature limits the dissipation of energy via plastic deformation of the epoxy polymer.…”
Section: Fracture Propertiesmentioning
confidence: 99%
“…Nevertheless, computational studies by Guild et al [45] have demonstrated that rubber particles cavitating at higher strains cause a far more complex shear-band dissipation mechanism and this can offset the loss of effectiveness of the void growth mechanisms.…”
Section: The Bulk Epoxy Polymersmentioning
confidence: 99%